Information and Communication Technologies in tourism - Ráthonyi, Gergely (Acta Agraria Debreceniensis, 2011)
Technological progress and tourism have gone hand in hand for years. Information communication technology (ICT) and tourism are two of the most dynamic motivators of the emerging global economy. Tourism can be considered as one of the most profitable sectors of the Hungarian economy, and in rural areas it is often the only successful economic activity.Development of ICTs and the expansion of the Internet have changed dramatically in the past few decades. This process is noticeable inHungary, as well. Platform of tourism increasingly get to the Internet nowadays, which is vitally important because tourism is an information-intense industry. Therefore, it is critical to understand changes in technologies in order to maintain the crucial role of this sector in the Hungarian economy.The aim of my study is to support the significance of tourism in Hungary and especially in the North Plain Region with the help of statistical data. Then, I try to show how ICTs appear in this sector and emphasize the role of these tools with some concrete examples.